Analyzing the Application of the Problem-Based Learning Model in Office Management and Business Services Subjects - Selviana, Maria; Puspasari, Durinta (Journal of Office Administration : Education and Practice, 2023)
This study was conducted to know the application of the problem-based learning model in the subject of office management and business services in class 10 APK 2 SMK PGRI 2 Sidoarjo. The learning model is a guide that teachers use to implement or organize learning in the classroom. The problem-based learning model is a learning model that can improve students' active thinking skills in solving problems in learning to make learning activities centered on students learning actively and independently in teaching and learning activities. The subject of Office Management and Business Services (MPLB) is a grade 10 subject in the office management automation expertise program, which contains competencies that underlie the mastery of office work and business services expertise. This research was conducted at SMK PGRI 2 Sidoarjo using descriptive qualitative research, with data collection techniques namely observation, interviews, and documentation. The research subjects used were seven APK 2 10th-grade students as class representatives and two Office Management and Business Services subject teachers. The results of this study show that applying the problem-based learning model can improve students' ability to think critically when solving problems and can play an active role in learning office management and business services subjects. And the learning process in the classroom is also more student-centered.